Political theology and political form: power, contingency, authority, belief. Issue 3 (2nd July 2016) - Rasch, William
Abstract : The paper argues that Carl Schmitt's notion of political theology is descriptively concerned with elucidating structural analogies between the basal self-description of an epoch and its various social institutions, not least the political. His political theology is critically interested in positing a functional equivalence between the idea of the historic Roman Church and the modern state. To explore this posited equivalence, the paper investigates various theological tropes that become 'secularized, ' including the medieval distinction between absolute and ordained power, the medieval 'discovery' of contingency and freedom, the co-dependence of authority and reason, and the 'manifestations of communion' (Hauriou) displayed by citizens of well-functioning states. The paper closes by wondering whether the semantics of our liberal age makes it impossible not only to accept, but even to understand the functional equivalencies Schmitt proposes. Yet, it also suggests that precisely this incomprehensibility might be a prod to further investigation rather than simple dismissal.